Medidas Antidumping e poder de mercado na América Latina - Lucas dos Santos Lourenço; Douglas Sad Silveira; Glauco Avelino Sampaio Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This text aims to provide evidence regarding the adverse effects of anti-dumping measures on the competitive market strategies in different sectors of economic activity. To map firms' strategic behaviour, as well as the evolution of their market power, our empirical model consists of estimating the Lerner index as a mark-up measure. To reach our goal, we use the Orbis database, with firm-level data between 2006 and 2014. Such measures are generated considering a time window in which industries achieved antidumping protection and had their exports punished in foreign markets. On average, our results suggest a positive relationship between anti-dumping barriers and the increase in firms' market power. This pattern proves to be especially greater for Latin America when compared to other emerging economies. Moreover, the effects on market power are more substantial in the long run and, depending on the specification of the country set, null in the short run.
Keywords: C33; D22; D43; F12; F13; 330; antidumping; Lerner's index; market competition; market power